Security of sanitizable signatures revisited - Brzuska, Chris; Fischlin, Marc; Freudenreich, Tobias; Lehmann, Anja; Page, Marcus; Schelbert, Jakob; Schröder, Dominique; Volk, Florian (2009)
Sanitizable signature schemes, as defined by Ateniese et al. (ESORICS 2005), allow a signer to partly delegate signing rights to another party, called the sanitizer. That is, the sanitizer is able to modify a predetermined part of the original message such that the integrity and authenticity of the unchanged part is still verifiable. Ateniese et al. identify five security requirements for such schemes (unforgeability, immutability, privacy, transparency and accountability) but do not provide formal specifications for these properties. They also present a scheme that is supposed to satisfy these requirements. Here we revisit the security requirements for sanitizable signatures and, for the first time, present a comprehensive formal treatment. Besides a full characterization of the requirements we also investigate the relationship of the properties, showing for example that unforgeability follows from accountability. We then provide a full security proof for a modification of the original scheme according to our model. © International Association for Cryptologic Research 2009.

Towards a lifecycle oriented design of infrastructure by mathematical optimization - Kufner, Tobias; Leugering, Günter; Martin, Alexander; Medgenberg, J.; Schelbert, Jakob; Schewe, Lars; Stingl, Michael; Strohmeyer, Christoph; Walther, Maximilian (Optimization and Engineering, 2019)
Today’s infrastructures are mainly designed heuristically using state-of-the-art simulation software and engineering approaches. However, due to complexity, only part of the restrictions and costs that show up during the lifecycle can be taken into account. In this paper, we focus on a typical and important class of infrastructure problems, the design of high-pressure steam pipes in power plants, and describe a holistic approach taking all design, physical, and technical constraints and the costs over the full lifecycle into account. The problem leads to a large-scale mixed-integer optimization problem with partial differential equation (PDE) constraints which will be addressed hierarchically. The hierarchy consists of a combinatorial and a PDE-constrained optimization problem. The final design is evaluated with respect to damage, using beam models that are nonlinear with respect to kinematics as well as constitutive law. We demonstrate the success of our approach on a real-world instance from our industrial partner Bilfinger SE.<br
Keywords: Structural optimization; Lifecycle oriented design; Mixed integer nonlinear programming